AN ASSESSMENT OF THE INFLUENCE OF CLASSROOM MATERIAL SUPPORT ON GENDER EQUITY IN EDUCATION IN PRIMARY SCHOOLS IN ISINYA SUB-COUNTY, KAJIADO COUNTY - Arogo, Kennedy Odhiambo; Mugwe, Dr. Mary; Thinguri, Dr. Ruth (African Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to assess the influence of classroom material support as an education production function on gender equity in education in Isinya Sub-County, Kajiado County-Kenya. Methodology: The study employed production function and structural functionalism theories. It adopted pragmatic (mixed) approach methodology. Concurrent triangulation research design was used to conduct the study. The data analysis was carried out by comparing the data collected from both questionnaires and interview schedules. The triangulation research design helped to address issues that overlap from both quantitative and qualitative data. The target population of the study was 3258 which consisted of 1896 class seven pupils, 1236 teachers, 122 Headteachers, 3 Sub-County Quality Assurance and Standards Officers (SCQASOs) and 1 Sub-County Director of Education (SCDE). From the target population, the researcher used simple random sampling to select 60 pupils; proportionate sampling was used to select 124 teacher respondents. 12 Headteachers were selected using proportionate sampling procedure. 3 ZQASOs and 1 SCDE were purposely selected giving a total of 200 respondents. Questionnaires were used to collect data from the learners, teachers and headteachers while the interview was for the SCDE and ZQASOs. Findings: Classroom material support is not to the mark. The state of the number of materials is not enough neither is the material provision done with gender equity in mind. Schools with adequate materials tend to thrive in gender equity in education while those that either have inadequate or ill gender sensitive materials are single gender dominated in many areas. Therefore, this affirms that classroom material support influences gender equity in education. Unique Contribution to Theory, Policy and Practice: When doing procurements, the personnel, government and non governmental agencies concerned with matters education materials support should take into consideration materials that encourage learners of both genders. Boys and girls should be provided with the required materials so as to enhance gender equity in education.